Analysis of results of tests carried out on earth test pieces - Julián Salas; María Jesús Guinea; Juan Diego Bernal (Materiales de Construccion, 1988)
A series of test pieces of 4x4x16 were prepared from Red Earth from Soria, the physical-chemical characteristics of which are given. The effect of each of the following upon the test pieces was studied: increasing the amount of cement on different earth/sand proportions; the type of cement; the variation of the cement proportion maintaining constant earth/sand proportions. In each case the bending-tensile and compressive strengths are given, and well as interrelationships between them.